2012
DOI: 10.1016/j.atherosclerosis.2011.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with n-6 PUFA protects against subsequent high fat diet induced atherosclerosis—Potential role of oxidative stress-induced antioxidant defense

Abstract: Objectives Recent evidence suggests that oxidative stress can promote antioxidant defense and thus be athero-protective. n-6 Polyunsaturated fatty acids (n-6 PUFA) are more prone to oxidation, compared to monounsaturated fatty acids (MUFA) and yet have proven anti-atherosclerotic effects. In this study, we tested whether early exposure to a diet rich in n-6 PUFA, compared to a MUFA rich diet would reduce lesion burden, even with subsequent exposure to a high fat, high cholesterol diet (HF). Further, we tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
1
11
0
2
Order By: Relevance
“…SS mitochondria, localized just beneath the sarcolemmal membrane [18], may be more susceptible to damage by HFD-induced increased fatty acid, because lipid content decreases exponentially from immediately below the sarcolemma toward the central region of the muscle fiber [26]. In addition, distinct stages in the progression of the pathophysiology of mitochondrial damage induced by dietary changes might range from initial adaptive to more chronic maladaptive changes [8,21]. Therefore, we speculate that IMF mitochondria may be at a compensatory state after 8 weeks HFD in our study.…”
Section: Discussionmentioning
confidence: 98%
“…SS mitochondria, localized just beneath the sarcolemmal membrane [18], may be more susceptible to damage by HFD-induced increased fatty acid, because lipid content decreases exponentially from immediately below the sarcolemma toward the central region of the muscle fiber [26]. In addition, distinct stages in the progression of the pathophysiology of mitochondrial damage induced by dietary changes might range from initial adaptive to more chronic maladaptive changes [8,21]. Therefore, we speculate that IMF mitochondria may be at a compensatory state after 8 weeks HFD in our study.…”
Section: Discussionmentioning
confidence: 98%
“…In another study, Agoramoorthy et al (2007) proved that Fatty acid Methyl Esters (FAME) from Excoecaria agallocha L. that was detrimental to Bacillus subtilis and S. aureus (MIC: 0.125 mg/ml) contained less of linoleic and oleic acids (3.13 and 1.71 %) ) and more of palmitic acid (56.02 %) when compared to our study. It has been proved that unsaturated fatty acids (especially PUFAs) help to reduce cholesterol formation or deposition and hence to decrease the risks of atherosclerosis and other heart disease (Penumetcha et al 2012). The susceptibility of Gram positive bacteria to H. suaveolans oil compared to Gram negative species might be due to the presence of hydrophilic outer membrane in the latter, mainly with regard to the presence of lipoproteins and lipopolysaccharides in the cell wall which form a barrier to hydrophobic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of studies, only F2-isoprostane or 8-isoprostane was measured by ELISA in blood or urine and seldom in tissues, which gave often discordant results. These studies have reported either increased (Zhu et al, 2008) or unchanged or (Petersson et al, 2010) even decreased (Penumetcha et al, 2012) isoprostane levels with HF or HF/HS diets in human or rodent models.…”
Section: Discussionmentioning
confidence: 99%